Alum-doped silicon dioxide aerogel and preparation method thereof
Through alum doping, the formation of cubic quartz is induced, and the problems of poor mechanical properties and low thermal stability of SiO2 aerogel are solved, and a high density and high thermal conductivity silica fiber aerogel is achieved, suitable for structural support and thermal isolation etc.
Patent Information
- Application Number
- CN202411085495.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2024-12-24
AI Technical Summary
SiO2 aerogel has poor mechanical properties and low thermal stability, which limits its applications in structural support, load bearing and thermal isolation.
SiO2 aerogel was prepared by alum doping. Alum induced the formation of cubic quartz and improved the thermal stability of SiO2 aerogel. The specific method includes mixing polyvinylpyrrolidone aqueous solution, alum and phosphoric acid with tetraethyl silicate, centrifugal spinning, and subsequent sintering in a muffle furnace, adjusting the sintering temperature and time to obtain high density and high thermal conductivity silicon dioxide. Fiber aerogel.
Alum doping significantly improves the thermal stability and mechanical properties of silica aerogels, enhances its durability at high temperatures, and is suitable for large-scale production due to its easy access and low cost.
Smart Images

Figure CN119176562A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of aerogel preparation, and in particular to an alum-doped silica aerogel and a preparation method thereof. Background Art
[0002] As an important functional material, SiO2 aerogel has been widely studied and applied in various fields in recent years. However, it still has problems and defects in many aspects, which limits its further development and application in some key applications. First, SiO2 aerogel usually has a low density and a high specific surface area, but its mechanical properties are relatively poor, and it is prone to compression deformation and fracture, which limits its practical application in structural support, load bearing, etc. In this regard, researchers have begun to work on improving the mechanical properties of SiO2 aerogel, and have enhanced its strength and toughness by changing the preparation process, adding suitable reinforcing agents, or doping other materials to meet the requirements of mechanical properties in different application scenarios. Secondly, SiO2 aerogel is prone to thermal decomposition, shrinkage, or loss of pore structure above 1000°C, resulting in low thermal stability, which limits its application in thermal isolation, refractory materials, etc. In order to overcome this problem, researchers are looking for new preparation methods and improved processes to improve the thermal stability of SiO2 aerogel. Summary of the invention
[0003] In order to solve the problem of poor thermal stability of SiO2 aerogel in the prior art, the present invention adopts alum doping to prepare SiO2 aerogel, and alum induces the formation of cristobalite to improve the thermal stability of SiO2 aerogel.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] The first aspect of the present invention provides a method for preparing alum-doped silica aerogel, comprising the following steps:
[0006] (1) mixing and stirring a polyvinyl pyrrolidone aqueous solution, alum and phosphoric acid, then adding tetraethyl silicate and continuing to stir to obtain a spinning solution;
[0007] (2) centrifugally spinning the spinning solution to obtain an aerogel precursor;
[0008] (3) placing the aerogel precursor into a muffle furnace for sintering, and obtaining silica fiber aerogel after cooling.
[0009] Preferably, in step (1), the concentration of polyvinyl pyrrolidone in the spinning solution is 10-20 wt %.
[0010] Preferably, in step (1), the pH value of the spinning solution is 3-4.
[0011] Preferably, in step (1), the molar ratio of alum to tetraethyl silicate is 1:(20-60).
[0012] Preferably, in step (2), during the centrifugal spinning process, the rotation speed of the centrifugal spinning equipment is adjusted to 180-220 rpm, the solution is sucked into the syringe using a syringe, the spinning solution in the syringe is added to the spinning disk, and then the rotation speed of the spinning machine is adjusted to 4000-6000 rpm.
[0013] Preferably, in step (3), the heating rate of sintering is 4-6°C / min.
[0014] Preferably, in step (3), the sintering temperature is 1000-1500° C., and the sintering time is 1-5 h.
[0015] The second aspect of the present invention provides an alum-doped silica aerogel, which is prepared by the alum-doped silica aerogel preparation method.
[0016] Preferably, the density of the alum-doped silica aerogel is 10-20 mg·cm -3 .
[0017] Preferably, the thermal conductivity of the alum-doped silica aerogel is 0.02-0.03 W / (m·K).
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] In the process of preparing silica aerogel, alum plays an important role as an inducing agent. + It has the effect of inducing amorphous silica to become quartz; in addition, the Al in alum 3+ Alumina particles can also be formed. Both quartz and alumina particles have the function of improving the heat resistance of silica micro-nano fiber aerogel. In addition, alum, as a common chemical, is inexpensive and easy to obtain, making it suitable for large-scale production of aerogels. Secondly, alum can interact with silicon sources in aqueous solution to promote the formation and structural regulation of aerogels, giving them better pore structure and performance. In addition, alum has high stability in aqueous solution and is not prone to side reactions, which is conducive to the preparation of high-quality aerogel materials. Finally, the preparation process of alum as an inducer is relatively simple, easy to operate and control, and is suitable for the preparation of different types of aerogels. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The actual picture of aerogel precursor before and after sintering;
[0021] Figure 2Density of silica micro-nano fiber aerogel at different annealing times (a) and alum doping amounts at different molar ratios (b);
[0022] Figure 3 is the thermal conductivity of silica micro-nano fiber aerogel at different densities;
[0023] Figure 4 To test the high temperature resistance of alum-doped and undoped silica micro-nano fiber aerogels;
[0024] Figure 5 This is the SEM image of silica micro-nano fiber aerogel after different high temperature resistance tests;
[0025] Figure 6 This is the SEM image of silica micro-nano fiber aerogel after different high temperature resistance tests;
[0026] Figure 7 This is the fiber diameter distribution diagram of silica micro-nano fiber aerogel in different high temperature resistance tests;
[0027] Figure 8 The fiber diameter changes of silica micro-nano fiber aerogels in different high temperature resistance tests;
[0028] Fig. 9 XRD patterns of two kinds of silica micro-nano fiber aerogels doped with alum and alumina;
[0029] Fig.10 XRD patterns of silica micro-nano fiber aerogels at different annealing times and different molar ratios of alum doping;
[0030] Fig.11 The EDS spectrum of silica micro-nano fiber aerogel without alum (a) and with alum (b);
[0031] Fig.12 The graph of the concentration changes of aluminum ions and potassium ions in silica micro-nano fiber aerogels doped with different concentrations of alum;
[0032] Fig.13 The low magnification SEM images of silica micro-nano fiber aerogels doped with different concentrations of alum;
[0033] Fig.14 The SEM images of silica micro-nano fiber aerogels doped with different concentrations of alum are shown at a scale of 50 μm.
[0034] Fig.15 The SEM images of silica micro-nano fiber aerogels doped with different concentrations of alum are shown at a scale of 25 μm.
[0035] Fig.16This is a statistical diagram of the diameter distribution of silica micro-nano fiber aerogels doped with different concentrations of alum;
[0036] Fig.17 The SEM images of the surface of silica micro-nano fiber aerogels doped with different concentrations of alum;
[0037] Fig.18 SEM images of silica micro-nano fiber aerogels at different annealing times (scale: 500 μm);
[0038] Fig.19 The low magnification SEM images of silica micro-nano fiber aerogels at different annealing times;
[0039] Fig. 20 The SEM images of silica micro-nano fiber aerogels at different annealing times (scale bar: 25 μm);
[0040] Fig.21 The diameter distribution statistics of silica micro-nano fiber aerogels doped with different annealing times;
[0041] Fig. 22 The SEM images of the silica micro-nano fiber aerogel fiber surface at different annealing times;
[0042] Fig.23 This is a graph showing the diameter change of silica micro-nano fiber aerogel under different alum doping concentrations and different annealing times. DETAILED DESCRIPTION
[0043] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0044] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0045] Example 1
[0046] Solvent configuration: Alum is added to a polyvinyl pyrrolidone (PVP) aqueous solution (mass fraction 15wt%), with 10g of polyvinyl pyrrolidone (PVP) aqueous solution as the standard, the mass of alum added is x, x=0.113, 0.135, 0.169, 0.225, 0.338g, 0.02g of phosphoric acid is added, and mechanical stirring is performed at room temperature at a speed of 500rpm. Through mechanical stirring, the PVP powder is evenly dispersed in the aqueous solution, which accelerates the dissolution rate of PVP and ensures that PVP is fully dissolved in water to form a transparent solution. By adding 0.02g of phosphoric acid, the pH value of the solvent is adjusted between 3-4 to ensure that the tetraethyl silicate (TEOS) solution undergoes a hydrolysis reaction at the most suitable pH.
[0047] Preparation of spinning solution: Add 3g of tetraethyl silicate (TEOS) solution to the prepared PVP aqueous solution for hydrolysis reaction, and stir mechanically at room temperature at a speed of 500rpm. When the stratification of the PVP aqueous solution and the TEOS solution completely disappears or when evenly distributed bubbles are formed inside the solution, it means that the TEOS is completely hydrolyzed and spinning can be carried out. Mechanical stirring can ensure that TEOS is in full contact with water and promote the uniformity of the hydrolysis reaction; mechanical stirring can also increase the mixing degree of the reaction system, accelerate the reaction rate between TEOS and water, and thus shorten the reaction time.
[0048] Centrifugal spinning: After the hydrolysis of TEOS is completed (the solution has no obvious stratification or the bubbles in the solution are evenly distributed), centrifugal spinning is performed. The speed of the centrifugal spinning equipment is adjusted to 200rpm, the solution is sucked into the syringe using a syringe, and the spinning solution in the syringe is added to the spinning disk. Then the speed of the spinning machine is adjusted to 5000rpm. The purpose of injecting the spinning solution at 200rpm is to make the spinning solution in the spinning disk evenly distributed, avoid excessive aggregation or accumulation of the solution in the syringe or on the spinning disk, and ensure the uniformity and stability of the fiber; in addition, this operation can also ensure the balance of the spinning disk, avoid violent spraying or oscillation of the solution during the spinning process, and is conducive to the formation and curing of the fiber. The aerogel precursor is collected.
[0049] The aerogel precursor obtained by spinning was subjected to a high-temperature sintering treatment of 1000°C in a muffle furnace, the heating condition was set to 5°C / min, and an annealing treatment was performed for 0, 1, 2, 3, 4, and 5h. After natural cooling, the silica fiber aerogel was obtained.
[0050] The parameters of different samples in Example 1 are shown in Table 1 below.
[0051] Table 1
[0052] serial number Tetraethyl silicate(g) Alum(g) Molar Ratio Annealing time 1-1 3.0g 0.000g 0:1 2h 1-2 3.0g 0.113g 60:1 2h 1-3 3.0g 0.135g 50:1 2h 1-4 3.0g 0.169g 40:1 2h 1-5 3.0g 0.225g 30:1 2h 1-6 3.0g 0.338g 20:1 2h 2-1 3.0g 0.169g 40:1 0h 2-2 3.0g 0.169g 40:1 1h 2-3 3.0g 0.169g 40:1 2h 2-4 3.0g 0.169g 40:1 3h 2-5 3.0g 0.169g 40:1 4h 2-6 3.0g 0.169g 40:1 5h
[0053] The actual pictures of the aerogel precursors prepared by No. 2-3 in Example 1 before and after sintering are as follows Figure 1 Figure a is a picture of the object before sintering, and figure b is a picture of the object after sintering.
[0054] The density of silica fiber aerogels under different annealing times and different molar ratios of alum doping is shown in Figure 2. Figure 2 As shown, Figure 2 As shown in (a), when the doping amount of alum remains unchanged, the density of the silica micro-nano fiber aerogel hardly changes with the change of the annealing time of the silica micro-nano fiber aerogel precursor, and the density is always around 17 mg cm -3 This indicates that the change of annealing time will hardly cause the change of the density of silica micro-nano fiber aerogel. The possible reasons are as follows: the crystal structure may not change significantly during the annealing process, which will not have a significant impact on the density. The pore structure is likely to have no significant change, so the impact on the density is small. Figure 2 As shown in (b), the annealing time of the silica micro-nano fiber aerogel precursor is controlled to remain unchanged, and the alum doping amount is changed. As the alum doping amount increases, the density of the silica micro-nano fiber aerogel generally shows an upward trend, which shows that the doping of alum will lead to a change in density. As the alum content increases, the density of the silica micro-nano fiber aerogel increases. The possible reasons are analyzed as follows: alum is introduced into the silica micro-nano fiber aerogel as an additive, and its density is usually high; therefore, as the alum content increases, the total mass added to the aerogel increases, resulting in an increase in the overall density of the aerogel. The doping of alum may change the crystal structure of the silica micro-nano fiber aerogel; the newly formed crystal structure may have a higher density, resulting in an increase in the density of the aerogel. The doping of alum may change the microscopic pore structure of the silica micro-nano fiber aerogel.
[0055] The silica fiber aerogels of samples No. 2-3 were extruded, and the silica micro-nano fibers were measured to obtain different densities of silica fiber aerogels. The thermal conductivity of silica micro-nano fiber aerogels at different densities was tested, such as Figure 3 , the thermal conductivity of silica micro-nano fiber aerogel was measured to be about 0.024-0.027W / (m·K), which is close to that of air. This similarity may be due to the fact that the microstructure and composition of silica aerogel are similar to the properties of air. As a low-density, porous material, silica aerogel has an open pore structure, a long heat conduction path, and the gas in it also affects heat conduction, resulting in its thermal conductivity being close to that of air. In addition, silica aerogel is mainly composed of oxygen and silicon elements, while air is mainly composed of oxygen, nitrogen, etc., and has certain similarities in composition, which also provides some possibilities for the similar thermal conductivity of the two.
[0056] The heat resistance of silica fiber aerogels with a molar ratio of alum to TEOS of 1:40 and annealing time of 2 hours and silica fiber aerogels without alum and annealing time of 2 hours at different temperatures were tested. The test results are as follows Figure 4 As shown. Figure 4 It can be observed that the silica fiber aerogel without alum undergoes deformation and shrinkage at high temperature (over 1400°C), which is due to the physical properties of amorphous silica. Silica undergoes phase change or crystallization at high temperature, which causes its structure to change and shrink. In contrast, the silica fiber aerogel doped with alum exhibits better temperature resistance. This is because the doping of alum induces the formation of cristobalite, which has a high melting point and good high temperature resistance. Below 1500°C, the shape of the silica fiber aerogel doped with alum hardly changes, with only a small amount of mass loss, indicating that the doping of alum does play a role in improving the temperature resistance. However, when the temperature reaches 1550°C, the silica fiber aerogel doped with alum, like the silica fiber aerogel without alum, undergoes deformation and shrinkage, and loses its original performance. This may be because the silica in the alum-induced silica fiber aerogel is amorphous and coexists with quartz phase. At this temperature, quartz cannot effectively protect the silica fiber aerogel from high temperature, causing it to lose stability. Then, the samples of the alum-doped silica micro-nano fiber aerogel after high temperature resistance test were subjected to SEM test. Figure 5-6 As shown, from Figure 5 It can be observed that the silica fiber aerogel has a certain degree of fracture and damage after high-temperature calcination. With the increase of calcination temperature, the degree of damage of silica fiber aerogel increases. Many fibers calcined at 1550°C show fractures, and also show fusion and coarsening. The possible reason is that with the increase of calcination temperature, the temperature inside the silica fiber aerogel will also increase, causing the gas inside to expand due to heating; since silica fiber aerogel is a porous material, there are a large number of tiny pores and channels inside, which will limit the expansion of the gas and cause high pressure inside. The thermal expansion coefficient of silica fiber aerogel is large. When heated, the material will show obvious volume expansion and fuse together at high temperature. Since the bond between the fibers is not very strong, the interaction between the fibers is affected during the calcination process, making the material prone to fracture and damage. When calcined at 1550°C, the thermal stress and thermal expansion effect reached the critical value, resulting in the inability of the bond between the fibers to withstand the stress generated inside, resulting in almost all fibers breaking. From Figure 6It can be seen that when the calcination temperature is 1400℃, the fiber surface is rough and accompanied by a small number of holes. It can be speculated that this phenomenon may be due to the fact that potassium ions easily generate potassium oxide at 600-800℃, and potassium oxide volatilizes under the action of high temperature, resulting in holes on the fiber surface. When the calcination temperature is 1450℃, it can be seen that there is a phenomenon similar to the healing of holes on the fiber surface. It may be due to the end of the potassium oxide volatilization process at high temperature, which stops the formation of holes, and at high temperature, the fiber surface material may partially melt or flow, resulting in the holes being filled or "healed". When the calcination temperature is 1500℃ and 1550℃, there are no more holes on the fiber surface, but the surface is still very rough. This may be because at higher temperatures, the volatilization process of gas or potassium oxide has ended, so no new holes will be generated; and the fiber surface material may further sinter or melt, causing the surface to become rougher and not smooth, or the structure inside the fiber changes, resulting in changes in surface morphology and increased surface roughness.
[0057] by Figure 5 As the standard, the diameter distribution diagram of the silica fiber aerogel after calcination at different temperatures was statistically analyzed. The results are as follows Figure 7 As shown in Figure 2, the diameter distribution of the fibers is relatively regular. The diameter distribution of the fibers in the silica fiber aerogel is plotted as the temperature changes. Figure 8 ,Depend on Figure 8 It can be observed that as the temperature rises, the fiber diameter gradually increases. The following three reasons may be speculated. First, from a thermodynamic point of view, the system tends to be in the state of lowest energy, that is, the lower the free energy of the system, the more stable it is. At high temperatures, the surface energy and volume energy of the fiber will increase, and by increasing the fiber diameter, the surface area can be reduced, thereby reducing the surface energy of the fiber. Therefore, the fiber spontaneously tends to be thicker to reach a lower energy state. In addition, fiber coarsening can also reduce the interfacial energy, which will affect the stability of the system when the fiber contacts other materials. By increasing the fiber diameter, the interfacial area can be reduced, thereby reducing the interfacial energy and making the system more stable. Second, at high temperatures, the silica material inside the fiber may be partially sintered, resulting in an increase in the fiber diameter, that is, the material partially melts or crystallizes at high temperatures and connects to each other to form larger crystals or agglomerates. This sintering process will increase the diameter of the fiber because the fiber surface material flows and rearranges at high temperatures, making the fiber denser. The third possibility is that at high temperatures, the material will expand, resulting in an increase in the diameter of the fiber. This expansion phenomenon may be due to the thermal expansion effect inside the material, or it may be due to the expansion and release of potassium oxide in the material.
[0058] Comparative Example 1
[0059] In this comparative example, based on Example 1, alumina was selected as a dopant to prepare silica aerogel. The doping content of alumina is shown in Table 2 below. The preparation method is consistent with the preparation method of alum-doped silica fiber aerogel. Unlike this, it is difficult to generate fibers during spinning, and the spinnability is poor. Possible reasons are that the solution lacks sufficient viscosity, resulting in the inability to effectively stretch and form fibers during rotation; the alumina particles are unevenly dispersed in the PVP solution, resulting in the uniformity of the fibers being affected during the spinning process, making it difficult to form a continuous fiber structure; or the needle of the centrifugal spinning is too thin, resulting in the inability to smoothly form fibers.
[0060] Table 2
[0061]
[0062]
[0063] The XRD patterns of samples No. 2-3 in Example 1 and samples No. 3-4 in Comparative Example 1 are as follows: Fig. 9 As shown, in the alum-doped sample, an obvious crystallization peak appeared, which indicates that the components in alum may promote the crystallization process of silica. In contrast, in the alumina-doped sample, there is only a diffuse peak and no obvious crystallization peak. This suggests that the silica in the alumina-doped sample still remains in an amorphous state, and no obvious crystallization occurs during the heating to 1000°C and insulation process. Therefore, it can be inferred that the potassium ions in alum play a role in inducing the crystallization of silica, while in the alumina-doped sample, alumina does not cause the crystallization of silica, but only shows a diffuse peak, which eliminates the possibility that the aluminum ions in alum induce the crystallization of silica. Fig. 9 As shown, the XRD spectrum of amorphous silica has only one diffuse scattering peak, while the XRD spectrum of crystalline silica in the quartz phase has a characteristic peak at 21.604° corresponding to the (111) plane, a characteristic peak at 35.626° corresponding to the (220) plane, a characteristic peak at 22.003° corresponding to the (222) plane, and a characteristic peak at 56.176° corresponding to the (331) plane.
[0064] Fig.10 The XRD results of silica micro-nano fiber aerogels with different annealing times and different molar ratios of alum doping are shown in Figure 2. Fig.10(a) is the XRD spectrum of silica micro-nano fiber aerogel under different annealing times. By observing the characteristic peak at 21.604° on the (111) plane, it can be found that when the annealing time is 0h, there is almost no crystallization peak, and the silica is almost entirely in an amorphous state; when the annealing time is 1h, the characteristic peak at 21.604° is a small peak on the basis of a diffuse scattering peak, indicating that when the annealing time is 1h, grains are generated, but the generated grains are small and mixed with amorphous silica; when the annealing time exceeds 2h, a large number of grains are generated in the silica micro-nano fiber aerogel.
[0065] When the annealing time is different, the degree of induction of potassium ions on amorphous silica is different, which will affect its crystallization degree. Fig.10 (b) is the change of the grain size of silica micro-nano fiber aerogel under different annealing times. The annealing time is from 0h to 1h to 2h and then to 3h. The grain size is getting bigger and bigger. This may be because in the initial annealing stage, the defects inside the crystal (such as dislocations, lattice defects, etc.) are gradually eliminated, the crystal structure begins to rearrange, and the grains gradually grow. It is due to the rearrangement of atoms inside the crystal and the migration of grain boundaries that the grain size gradually increases. When the annealing time reaches 4h, the grain size becomes smaller instead. This may be because when the annealing time reaches a certain extent, the grain boundary migration is restricted or recrystallization occurs. The restricted grain boundary migration means that the grain boundary cannot continue to move, thereby limiting the further growth of the grain; recrystallization may cause new small grains to form inside the original grain, resulting in a decrease in the overall grain size. After 5h, the grain size is consistent with that of annealing for 4h. This may be because when the annealing time continues to increase, the grain boundary energy is reduced and the grain grows again; under certain conditions, new grain boundaries are formed and reach a stable state, so that the grain size is similar to the previous size.
[0066] like Fig.10(c) is the XRD spectrum of silica micro-nano fiber aerogel under different alum doping amounts. By observing the characteristic peak at 10.802° on the (111) plane, it can be found that when alum is not doped, the XRD spectrum of silica micro-nano fiber aerogel has only one diffuse scattering peak, and no quartz is generated. Alum is added as an inducer. When the molar ratio of alum to TEOS is 1:60, an obvious crystallization peak can be observed; but when the molar ratio of alum to TEOS is continuously increased to 1:30, the crystallization peak disappears. When the molar ratio of alum to TEOS is increased to 1:20, the characteristic peak at 10.802° has a small peak on the basis of a diffuse scattering peak, and a small amount of crystals are generated. There are two possible reasons for the analysis, namely the influence of potassium ions and aluminum ions in alum on crystallization. On the one hand, when the molar ratio of alum to TEOS is 1:60, 1:50, and 1:40, the potassium ions in alum fully exert their role in inducing crystallization, prompting the silica crystal to form a quartz phase, so an obvious crystallization peak is observed in the XRD spectrum; as the molar ratio of alum to TEOS increases further, the potassium ions in alum may be excessive, resulting in the loss of balance in the control of the crystallization direction during crystal growth, thereby inhibiting the formation of crystal morphology and crystallization peaks. On the other hand, as the molar ratio of alum to TEOS increases further, the aluminum ions in alum may begin to inhibit crystallization; the aluminum ions in alum generate aluminum oxide during sintering, and the interface between aluminum oxide and silica may inhibit the growth and crystallization process of the crystal. When the molar ratio is 20:1, the small peak appearing on the diffuse scattering peak may be a result of the regulation of the crystallization process. Under this condition, a certain number of crystal nuclei may be formed, but due to the presence of aluminum oxide, the crystal growth is inhibited to a certain extent, so the formed grains are relatively small, showing the form of small peaks.
[0067] The EDS images of sample No. 1-1 in Example 1 and sample No. 1-4 in Example 1 are as follows: Fig.11 As shown, Fig.11 (a) is undoped alum, Fig.11 (b) is doped with alum, such as Fig.11 (a) The silica nanofiber aerogel without alum contains only oxygen, silicon, and carbon, which is consistent with expectations. Fig.11 (b) It can be found that after doping with alum, in addition to oxygen, silicon, and carbon, there are also potassium and aluminum elements in the silica micro-nano fiber aerogel, which is consistent with expectations. Fig.12As shown in the figure, with the increase of alum doping, the potassium and aluminum elements in the silica micro-nano fiber aerogel further increase; it can be further inferred that with the increase of alum doping, the aluminum ions in the silica micro-nano fiber aerogel begin to inhibit crystallization. The proportion of potassium in the silica micro-nano fiber aerogel without annealing time was measured by EDS. When the annealing time was 2h, the potassium element accounted for 2.678%; when the annealing time was 4h, the potassium element accounted for 2.641%; and when the annealing time was 5h, the potassium element accounted for 1.981%. It shows that with the increase of annealing time, potassium ions gradually decrease. It is speculated that the possible reason is that potassium ions gradually generate potassium oxide after long-term annealing treatment, and potassium oxide volatilizes at high temperature, resulting in a decrease in the proportion of potassium.
[0068] The SEM images of the experimental samples doped with different concentrations of alum were observed at low magnification, such as Fig.13 As shown, in the figure, af represents the molar ratio of alum to TEOS of 0:1, 1:60, 1:50, 1:40, 1:30, and 1:20 respectively. The potassium ions in alum play an important inducing role in the crystallization process of silica fiber aerogel, causing amorphous silica to gradually transform into a quartz structure. In the SEM image, the fibers show a relatively uniform distribution and form a relatively dense arrangement state. With the increase of alum concentration, the fiber distribution becomes more dense, which may be due to the addition of alum providing more crystallization nuclei and promoting the growth and arrangement of fibers. In the SEM image, the length and diameter of the fibers are relatively consistent, and the overall morphology is regular, showing a slender and slightly curved morphology. This morphological change may be related to the induction of alum. The potassium ions in alum may change the growth mode of silica or the formation of the crystal structure, resulting in a change in the fiber morphology. With the increase of alum concentration, the fibers become significantly thinner, which may be due to the increased alum concentration leading to the formation of more crystallization nuclei, affecting the growth and morphology of the fibers. In addition, no obvious impurities or contaminants were observed in the SEM images, which indicated that the purity of the samples was relatively high and the effectiveness of alum as an inducer was verified.
[0069] By observing the SEM image of silica micro-nano fiber aerogel with a scale bar of 50 μm ( Fig.14As shown in the figure, af represents the molar ratio of alum to TEOS (0:1, 1:60, 1:50, 1:40, 1:30, 1:20), which can provide a deeper understanding of the effect of alum concentration on fiber structure and morphology. As the alum concentration increases, it can be observed that the density of the fiber gradually increases, and the spacing between the fibers becomes closer. This may be because alum, as an inducer, promotes the crystallization process of silica, making the distribution of the fibers in the sample more compact and uniform. In the SEM image, the fibers present a slender and curved shape, uniform distribution and close arrangement. Although the fibers become significantly thinner and present a more slender shape with the increase of alum concentration, they still maintain good distribution and arrangement. This morphological change of the fiber may be related to the change of the silica crystal structure induced by alum, which in turn affects the growth and morphology of the fiber. In the SEM image, a small amount of liquid droplets present tiny protrusions on the fiber surface, but do not affect the overall morphology and structure of the fiber. These liquid droplets may be caused by residual solvents or surface tension during the preparation process, but have little effect on the structure and properties of the fiber. In addition, the fibers are relatively soft and flexible, without obvious hardness or stiffness, which may be related to their slender and curved shape and degree of crystallinity. Fig.15 This is the SEM image of silica micro-nano fiber aerogel with a scale bar of 25 μm.
[0070] The diameter of silica micro-nano fiber aerogel at different alum concentrations was measured using the SEM image of silica micro-nano fiber aerogel at a scale of 25 μm as the measurement standard. By measuring the silica micro-nano fiber aerogel at 1000 times, the diameter data of the fibers at different alum concentrations can be obtained, and a diameter distribution diagram can be drawn (such as Fig.16As shown in the figure, af represents the molar ratio of alum to TEOS of 0:1, 1:60, 1:50, 1:40, 1:30, and 1:20, respectively). It can be clearly seen from the diameter distribution diagram that at different alum concentrations, the fiber diameter of the silica micro-nano fiber aerogel is mainly distributed between 1-2.5 μm and presents a relatively concentrated characteristic. This concentrated distribution indicates that the fiber diameter in the sample has a certain uniformity and consistency, which is beneficial to the stability of the material and the controllability of the performance. However, despite the concentrated distribution of the fiber diameter, there is a certain degree of error in the diameter measurement due to the difference in the distribution of the fibers at far and near positions. The fiber diameter range between 1-2.5 μm is of great significance for silica micro-nano fiber aerogel materials. First, this size range is between the micron and submicron levels, with moderate size characteristics, which not only maintains the tiny size of the nanometer level, but also has the mechanical strength and stability of the micron level. Secondly, due to the slender morphology of the fiber, this diameter range brings a superior specific surface area, which is beneficial to improving the adsorption performance and reaction activity of the material. In addition, this diameter range is suitable for a variety of application fields, not only for micro-scale material modification and functional regulation, but also for macro-scale structural construction and engineering design, and has broad application prospects. Finally, the fiber diameter distribution is concentrated and uniform, indicating that the sample has good stability and repeatability, which is beneficial to the performance of the material in practical applications and engineering practice.
[0071] Observe the surface of silica micro-nano fiber aerogels doped with different concentrations of alum at high magnification. Fig.17 (af in the figure respectively represents the molar ratio of alum to TEOS of 0:1, 1:60, 1:50, 1:40, 1:30, and 1:20), which can provide a deep understanding of the morphological characteristics of the fiber surface. It can be clearly seen from the image that the fiber surface is relatively smooth, regular, and has no obvious roughness or unevenness. This surface morphology is crucial for silica fiber aerogel materials. The smoothness of the fiber surface may also be related to the crystal structure morphology induced by alum. The potassium ions in alum can promote the crystallization process of silica and form a more ordered and compact crystal structure. This ordered crystal structure may form a uniform and regular crystal film on the fiber surface, making the fiber surface appear smoother.
[0072] Observe the SEM images of silica micro-nano fiber aerogels at different annealing times (such as Fig.18, af in the figure represents annealing time of 0, 1, 2, 3, 4, and 5 hours respectively), which can provide a deep understanding of the effect of annealing time on fiber morphology. In these images, the fiber distribution is relatively uniform, showing a relatively dense arrangement state, its length and diameter are relatively consistent, the overall morphology is relatively regular, and it presents a more slender and slightly curved morphology. This regular fiber structure is crucial for the performance and application of the material. With the increase of annealing time, the density of the fiber is observed to increase, which may be due to the long-term high-temperature annealing process that promotes the rearrangement and growth of silica crystals, resulting in changes in fiber morphology. During the annealing process, the rearrangement and growth of crystals make the fiber structure more compact, and the cross-linking between fibers is also tighter, so the density of the fiber increases. In addition, annealing also helps to eliminate some residual organic matter or solvent residues in the preparation process, making the sample purer, which is also verified in the SEM image. No obvious impurities or contaminants were observed in the SEM image, indicating that the sample has a high purity. By regulating the annealing time, the structure and properties of silica micro-nano fiber aerogel can be effectively changed to meet the needs of specific application fields. SEM analysis results showed that the increase in annealing time had a significant effect on the morphology and density of the fibers, but no other obvious abnormalities were observed.
[0073] Observe the SEM image of silica micro-nano fiber aerogel at low magnification ( Fig.19 , af in the figure represents annealing time of 0, 1, 2, 3, 4, and 5 hours respectively), and the fiber diameter under different annealing times shows obvious changes. Except for the case where the annealing time is 0 hours, the fiber diameter under other annealing times is relatively uniform, which may be due to the rearrangement and growth of crystals during the annealing process, making the fiber diameter more consistent. During the annealing process, the stress inside the fiber is gradually released, which makes the crystal state of the fiber more stable, thereby making the fiber diameter more uniform. However, as the annealing time is extended to 5 hours, some fibers have a certain degree of fracture and damage. This may be due to the effect of annealing temperature on the internal structure and surface oxidation state of the fiber during long-term high-temperature annealing. Under high temperature conditions, the stress inside the fiber will gradually release, but if the annealing time is too long, uneven stress release may cause excessive local stress in the fiber, thereby causing fracture. In addition, long-term high-temperature annealing may also cause excessive oxidation on the fiber surface, making the fiber surface brittle and prone to fracture. Therefore, the appropriate annealing time is crucial to the performance and structure of silica micro-nano fiber aerogel. A moderate annealing time helps promote the crystal rearrangement and growth of the fiber, making the fiber size more uniform, but too long an annealing time may cause fiber breakage and damage, reducing the stability and reliability of the material. In summary, the annealing time needs to be precisely controlled during the material preparation process to achieve ideal material properties and structure.
[0074] Fig. 20 The SEM images of silica micro-nano fiber aerogels at different annealing times with a scale of 25 μm (af in the figure represent annealing times of 0, 1, 2, 3, 4, and 5 hours, respectively). The silica micro-nano fiber aerogels at a scale of 25 μm were used as the measurement standard, and the diameters of silica micro-nano fiber aerogels at different alum concentrations were counted. By measuring the silica micro-nano fiber aerogels, the diameter data of the fibers at different annealing times were obtained, and a diameter distribution diagram was drawn (as shown in FIG. Fig.21 As shown, af in the figure represents annealing time of 0, 1, 2, 3, 4, and 5 hours respectively). In the diameter distribution of silica micro-nano fiber aerogel under annealing time, although the fiber diameter distribution of each sample is relatively concentrated, there is still a certain degree of error. This error may be due to the difference in the arrangement of fibers in different samples, which affects the accuracy of diameter measurement. In terms of the influence of annealing time, through the observation of the diameter distribution diagram, it is found that the fiber distribution in samples under different annealing times is between 1.9-2.0μm, and the fiber diameter distribution is relatively concentrated, with almost no significant change. This shows that the length of annealing time does not significantly affect the thickness of the fiber. This may be because during the annealing process, the adjustment of the internal structure and crystal state of the fiber affects the morphology and properties of the fiber more, while the effect on the diameter is relatively small. In addition, the diameter distribution of the fiber is between 1.9-2.0μm, showing good consistency, indicating that the fibers in different samples have similar size characteristics, which is conducive to ensuring the stability and reliability of material performance even at different annealing times. The diameter of the fiber is about 1.9-2.0μm, which is relatively suitable for silica micro-nano fiber aerogel. Within this range, the fiber size is small enough to increase the specific surface area and surface activity of the material, and stable enough to maintain the structural and performance stability of the material. Therefore, the fiber in this diameter range is of great significance for the preparation and performance of silica micro-nano fiber aerogel.
[0075] When observing the surface of silica micro-nano fiber aerogel at high magnification, it can be seen that the morphology of the fiber surface has changed significantly (see Fig. 22, af in the figure respectively represents annealing time of 0, 1, 2, 3, 4, and 5 hours). When the annealing time is short, the fiber surface presents relatively smooth and regular shape characteristics, and there is no obvious roughness or unevenness. However, as the annealing time increases, especially after the annealing time is as long as 3 hours, 4 hours, and 5 hours, holes begin to appear on the fiber surface. This phenomenon may have multiple reasons and mechanism explanations. First, during the insulation process, there may be adsorbed or dissolved gases inside the fiber. As the temperature rises, these gases will gradually release to form bubbles. These bubbles gather and expand on the fiber surface, eventually leading to the formation of holes. In addition, long-term insulation may cause changes in the fiber structure, such as crystal growth, increased crystallinity, or loosening of the material. These structural changes may cause unevenness on the fiber surface, resulting in lower density in some areas, thereby forming holes. In addition, there is another possibility that potassium ions easily generate potassium oxide at 600-800℃, and potassium oxide volatilizes under the action of high temperature, which is consistent with the previous EDS test results. As the annealing time increases, the potassium element gradually decreases, resulting in holes on the fiber. Therefore, the effect of annealing time on the fiber surface morphology mainly stems from the release of gas and the change of fiber structure during the insulation process. As the annealing time increases, these factors will gradually increase, resulting in the phenomenon of holes on the fiber surface. Whether there are holes in the morphology of the fiber surface will have a significant impact on the performance and application of the fiber. First, fibers with holes on the surface may cause their mechanical properties to decrease. Holes as voids inside the fiber will reduce the effective cross-sectional area, thereby reducing the load-bearing capacity and tensile strength of the fiber. This makes the fiber more susceptible to external forces, which may increase the risk of fiber breakage or deformation. Secondly, fibers with holes on the surface may affect their surface properties. Holes make the fiber surface no longer smooth and uniform, but irregular and rough, which may affect the adhesion of the fiber to other materials. In certain application scenarios, such as the preparation of fiber-reinforced composite materials, surface holes may reduce the bonding strength between the fiber and the matrix, thereby affecting the overall performance of the composite material. In addition, when silica micro-nano fiber aerogel is used in thermal insulation materials, the presence of holes on the surface may have a positive effect on its thermal conductivity: Generally, the performance of thermal insulation materials depends on its ability to effectively reduce heat conduction. Surface holes can increase the surface area of the material, thereby increasing the contact area between the material and the surrounding environment, thereby increasing the scattering and radiation of heat; in addition, holes can also improve the thermal conductivity of the gas of the material, because the thermal conductivity of gas is usually much lower than that of solids. Therefore, the presence of holes may enhance the insulating properties of thermal insulation materials, making them more effective in reducing heat conduction, thereby improving the thermal insulation effect.
[0076] Comparison of the changes in fiber diameter of silica micro-nano fiber aerogels with different alum doping concentrations Fig.23(a) is shown. It is found that the diameter of the fiber doped with alum is lower than that of the fiber without alum doping. The reason may be that the doping of alum promotes the growth of silica crystals in the aerogel, and the formation of crystals usually leads to a decrease in the fiber diameter; compared with amorphous silica, quartz has a more regular crystal morphology and a higher crystallinity. This increase in crystallinity may lead to a thinner fiber diameter; the formation of cristobalite crystals may lead to an increase in grain boundaries, which are usually the parts with weaker mechanical properties in the material, and their existence may lead to a thinner fiber diameter; the formation of cristobalite crystals may affect the orientation of the fiber, increasing the growth rate of the fiber in certain directions, thereby leading to a thinner fiber diameter.
[0077] As the amount of alum doping increases, the diameter of the fiber begins to increase. The possible reason is that the potassium ions in alum affect the growth mode and rate of silica crystals. The increase in potassium ion concentration promotes the growth of crystals, causing the crystals to grow along the fiber growth direction, thereby increasing the fiber diameter. In addition, alum doping may regulate the proportion of components in the solution, affecting the formation mechanism of silica fibers, thereby causing changes in fiber diameter. However, when the alum content increases to a molar ratio of 1:30 with TEOS, the diameter begins to decrease dramatically. This may be caused by the inhibition of silica crystallization by alumina at 1:30, and the crystal growth is inhibited. As the alum content increases, the alumina content may also increase, exacerbating the inhibition of crystal growth. As a result, the fiber diameter is reduced. In addition, alumina may also form a coating on the surface of silica crystals, hindering the further growth of crystals, resulting in a reduction in fiber diameter.
[0078] Comparison of the fiber diameter changes of silica micro-nano fiber aerogels under different annealing times. Fig.23 (b). As the annealing time increases, it is observed that the diameter of the silica fiber aerogel does not change significantly, showing a slight upward trend. This phenomenon may be affected by a variety of factors. First, as the annealing time increases, the growth rate of the crystal may be affected to a certain extent, but this effect is not very significant, so the diameter of the fiber remains relatively stable or slightly increases. Secondly, as the annealing time increases, the crystal may gradually adjust its grain boundary structure, but the amplitude of this adjustment may be small and insufficient to cause a significant change in the fiber diameter. In addition, the material has a certain stability under certain conditions, and even if the annealing time is extended, the basic properties of the material may not change significantly, resulting in the fiber diameter remaining relatively stable. Finally, during the annealing process, the crystal may have a certain orientation effect, resulting in a slight increase in the crystal growth rate along certain directions, causing a slight upward trend in the fiber diameter. The combined effect of these factors has led to the fact that the annealing time has little effect on the change in fiber diameter, showing a slight upward trend.
[0079] Through the results of the effect of alum doping on the crystallization of silica micro-nano fiber aerogel, it can be seen that the crystallization mechanism of silica micro-nano fiber aerogel induced by different concentrations of alum involves multiple factors. The potassium ions and aluminum ions in alum have different effects on the crystallization of silica at different concentrations, resulting in different crystallization mechanisms at different concentrations. At low concentrations, the potassium ions in alum promote the transformation of amorphous silica to cristobalite by interacting with it. First, the addition of potassium ions enables smaller alkali metal ions to move more easily in silica, thereby promoting the formation of a crystalline phase. Secondly, the presence of potassium ions changes the formation and structure of Si-O bonds and forms negatively charged non-bridging oxygen by destroying the bridging oxygen of Si-O-Si; the negatively charged non-bridging oxygen reduces the connectivity of the silica network and reduces the energy required for the crystallization of amorphous silica. These mechanisms may lead to changes in the structure of silica, thereby affecting its crystallization behavior. In addition, aluminum ions can also form alumina particles, further improving the heat resistance of aerogels. At high concentrations, the interaction between cations and silica becomes more complicated. Among them, the addition of potassium ions will still induce the crystallization of silica micro-nano fiber aerogel, while the concentration of aluminum ions increases to form a large amount of aluminum oxide. High concentration of aluminum oxide will effectively inhibit the formation of quartz. Under the dual effects of potassium ions and aluminum ions, it is difficult for alum to induce the crystallization of silica micro-nano fiber aerogel at higher concentrations. Therefore, when alum is doped at a higher concentration, the interaction between cations in alum and silica becomes more complicated, resulting in the formation of different crystal phases or crystal structure regulation, thereby affecting the properties and structure of the aerogel.
[0080] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A method for preparing alum-doped silica aerogel, characterized in that: The following steps are involved: (1) mixing and stirring a polyvinyl pyrrolidone aqueous solution, alum and phosphoric acid, then adding tetraethyl silicate and continuing to stir to obtain a spinning solution; (2) centrifugally spinning the spinning solution to obtain an aerogel precursor; (3) placing the aerogel precursor into a muffle furnace for sintering, and obtaining silica fiber aerogel after cooling.
2. The method for preparing alum-doped silica aerogel according to claim 1, characterized in that: In step (1), the concentration of polyvinyl pyrrolidone in the spinning solution is 10-20wt%.
3. The method for preparing alum-doped silica aerogel according to claim 1, characterized in that: In step (1), the pH value of the spinning solution is 3-4.
4. The method for preparing alum-doped silica aerogel according to claim 1, characterized in that: In step (1), the molar ratio of alum to tetraethyl silicate is 1:(20-60).
5. The method for preparing alum-doped silica aerogel according to claim 1, characterized in that: In step (2), during the centrifugal spinning process, the rotation speed of the centrifugal spinning equipment is adjusted to 180-220 rpm, the solution is sucked into the syringe using a syringe, the spinning solution in the syringe is added to the spinning disk, and then the rotation speed of the spinning machine is adjusted to 4000-6000 rpm.
6. The method for preparing alum-doped silica aerogel according to claim 1, characterized in that: In step (3), the heating rate of sintering is 4-6°C / min.
7. The method for preparing alum-doped silica aerogel according to claim 1, characterized in that: In step (3), the sintering temperature is 1000-1500° C., and the sintering time is 1-5 hours.
8. An alum-doped silica aerogel, characterized in that: The alum-doped silica aerogel is prepared by the preparation method of any one of claims 1 to 7.
9. The alum-doped silica aerogel according to claim 8, characterized in that: The density of the alum-doped silica aerogel is 10-20 mg·cm -3 .
10. The alum-doped silica aerogel according to claim 8, characterized in that: The thermal conductivity of the alum-doped silica aerogel is 0.02-0.03 W / (m·K).
